2012
DOI: 10.1111/j.1753-0237.2012.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring oil price—exchange rate nexus for Nigeria

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
3
10
1
Order By: Relevance
“…In addition, oil price was found to be integrated of order one. This is consistent with the findings of Amano and van Norden (1998), Lizardo and Mollick (2010), Muhammad et al, (2011) and Adeniyi et al (2012). Thus, our result is consistent with the evidence of the non-stationary behavior of the exchange rate from the literature.…”
Section: Unit Rootssupporting
confidence: 95%
See 2 more Smart Citations
“…In addition, oil price was found to be integrated of order one. This is consistent with the findings of Amano and van Norden (1998), Lizardo and Mollick (2010), Muhammad et al, (2011) and Adeniyi et al (2012). Thus, our result is consistent with the evidence of the non-stationary behavior of the exchange rate from the literature.…”
Section: Unit Rootssupporting
confidence: 95%
“…While some of the studies have found a positive relationship between oil price and exchange rate -oil price shock leading to appreciation - Olomola and Adejumo, 2006;Chen and Chen, 2007;Adeniyi et al, 2012;Amano and van Noden, 1998;Beckmann and Czudaj, 2012;Englama et al, 2010, Jebin and Osu, 2012, Nikbakht, 2009, others have reported a negative relationship -oil price shock leading to depreciation- (Akram, 2004;Ghosh, 2011;Huang and Guo, 2007;Muhammad et al, 2011) or non-existing relationship (Akram and Holter, 1996;Bjørvik et al, 1998;Buetzer et al, 2012).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The role of oil price in explaining FOREX movement has been noted as far back as 1980s by scholars like Golub (1983) and Krugman (1983). Both authors found oil-exporting countries to experience FOREX appreciation during oil price rise, while there was FOREX depreciation during oil price falls (see Al-Mulali and Binti Che Sab (2012); Muhammad et al (2012)). The case was the reverse for oil-importing countries, where there was FOREX depreciation during oil price rise and FOREX appreciation during oil price falls.…”
Section: Introductionmentioning
confidence: 99%
“…This question has not been answered. Specifically, while empirical studies on the impact of crude oil price on economic growth and macroeconomic performance in Nigeria exist (see Chuku, 2012;Iwayemi & Fowowe, 2011;Muhammad, Suleiman, & Kouhy, 2012;Omojolaibi, 2014;Omojolaibi & Egwaikhide, 2014), the influence of crude oil price on the development of financial intermediation has not been considered. Understanding the relationship between crude oil prices and financial intermediary development could have a significant impact on the formulation and implementation of macroeconomic policies targeting financial sector development.…”
Section: Introductionmentioning
confidence: 99%